GENETIC VARIATION OF SALVIA JAPONICA THUNB. (LAMIACEAE) AND ITS RELATED SPECIES - Sudarmono Sudarmono; Hiroshi Okada (PTTI, 2011)
Sudarmono & Hiroshi Okada. 2011. Genetic variation of Salvia japonica Thunb. (Lamiaceae) and Its Related Species. Floribunda 4(2): 33–39. — Genetic variation between populations of Salvia japonica Thunb. (widely distributed species) and its genetic relationships to relative species (Lamiaceae) were analyzed using allozyme polymorphisms. The fact that all of 12 loci analyzed were polymorphic indicated high genetic variations in S. japonica. Mean of polymorphic loci (P%), mean number of alleles per locus (A), and expectedheterozygosity (He) compared to related Salvia species as well as out-crossing species were highly indicating genetic differentiation between populations. Total genetic diversity (HT = 0.469) majority partitioned within populations and genetic structure which possibly affected by protandry and almost selfincompatible, outcrossing features in S. japonica. Low gene flow (Nm = 0.268) was might be resulted from the movement of pollinators and effect of genetic drift on small, widely scatterred, isolated populations of S. japonica. UPGMA cluster analysis using Nei‘s genetic distance indicated that S. japonica has close genetic relation with S. isensis and S. lutescens.